PELATIHAN PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS FLIPBOOK BAGI GURU DI SD IT NUSA INDAH - nurhamimah rambe; Renni Ramadhani Lubis; Yusda Novianty; Dita Amelia (LPPM STKIP AL MAKSUM, 2023)
The purpose of the training activities is to increase teachers' knowledge about using flipbook based learning media. This training activity was attended by 19 people, including 2 lecturers and 1 student from STKIP Al Maksum Langkat, and 17 people consisting of school principals and IT Nusa Indah Elementary School teachers. The methods used in this training are the preparation stage, site survey, preparation of instruments, implementation of training activities, and evaluation stage. Based on the results of the training that had been conducted at SD IT Nusa Indah it was found that this training was very useful for teachers, because teachers gained new knowledge and experience in making flipbook based learning media to support the learning process in the classroom.